تراكم بعض المعادن الثقيلة في النباتات العلفية ومدى إفرازها في حليب الأبقار في منطقة بانياس (الساحل السوري) - دلا توفيق; شريف عبد اللطيف (Latakia University Journal -Biological Sciences Series, 2013)
سلامة الغذاء ومراقبة محتويات المنتجات الزراعية أمور ذات أهمية كبيرة بالنسبة للمستهلكين، نتيجة للوعي الغذائي، وحفاظاً على الصحة العامة و وقايتها من الأمراض. الهدف من هذه الدراسة معرفة تراكيز بعض المعادن الثقيلة (الرصاص- الكادميوم- النيكل- الكروم)، في بعض النباتات العلفية (البرسيم .Trifolium ssp، النجيلCynodon dactylon ، الشوفان Avena sativa L.)، ومدى إفرازها في حليب الأبقار في منطقة بانياس في الساحل السوري. تم جمع العينات النباتية وعينات الحليب من أربع مناطق تبعد مسافات محددة عن كل من مصفاة بانياس والمحطة الحرارية وتم تحضيرها على شكل محاليل وحللت بجهاز الامتصاص الذري Atomic Absorption Spectroscopy. بينت نتائج الدراسة أن تركيز الرصاص في عينات الحليب تراوح بين (0.017-0.021 mg/kg)، وتركيز الكادميوم (0.008- 0.012 mg/kg)، والنيكل 0.038- 0.041 mg/kg))، في حين كان تركيز الكروم (0.035-0.042 mg/kg)، وأظهر تركيز الرصاص والكادميوم في المناطق الثلاثة الأولى القريبة من مصدري التلوث المدروسين قيماً أعلى من حدود السماح الموصى بها من قبل الاتحاد الأوروبي (0.02 mg/kg) للرصاص و(0.01 mg/kg) للكادميوم, في حين كانت قيم المعادن في النباتات العلفية المدروسة ضمن الحدود المقبولة. بناءً على هذه المعطيات هناك ضرورة ملحة لمراقبة محتويات المعادن الثقيلة في المنتجات الغذائية وضبطها ، حرصاً على سلامة الغذاء، وحفاظاً على صحة الإنسان. Food safety and monitor of the contents of agricultural products are matters of great importance for consumers, as a result of food awareness, public health and disease prevention. The aim of this study is to know the concentrations of some heavy metals (lead - cadmium - nickel - chromium), in some fodder plants (Trifolium ssp., Cynodon dactylon., Avena sativa L.(, and the extent of its secreted in the milk of cows in the area of ​​Banias on the Syrian coast. Plant samples and milk samples were collected from four regions separated by a specific distance away from sources of pollution in the studied area. They were prepared in the form of solutions and analyzed by Atomic Absorption Spectroscopy device. The results of the study showed that the concentration of lead in the milk samples ranged between (0.017-0.021 mg / kg), and the concentration of cadmium (0.008-0.012 mg / kg), and nickel (0.038-0.041 mg / kg), while the concentration of chromium (0.035- 0.042 mg / kg). it also showed that the concentration of lead and cadmium in the first three areas near pollution sources were ​​higher than the recommended limits allowed by the EU European Union (0.02 mg / kg) for lead and (0.01 mg / kg) for cadmium, while the values ​​of other minerals in the forage plants studied were within acceptable limits. These results suggested that there is an urgent need to control the heavy metal contents of primary food products for food safety and public health.